Dielectric and ferroelectric properties of Pb(Zr0.53Ti0.47)O3 ceramics modified with Sr. Issue 187 (12th February 2018) - Kongphimai, J.; Photankham, W.; Phewphong, S.; Namthaisong, A.; Wattanasarn, H.
ABSTRACT: The (Pb1–x Srx )(Zr0.53 Ti0.47 ) O3 x = 0, 4.5, 6.0, 7.5 mol% were synthesized from PbO, SrCO3, ZrO2, TiO2 powders by solid state reaction. The crystal structure, density, hardness, dielectric and ferroelectric properties were investigated. Additionally, with Sr in the same position of Pb, showed that there is another alternative in the development of PZT piezoelectric materials and the improvement of dielectric and ferroelectric properties for PZT. It was found that the addition of Sr at x = 7.5 mol% makes dielectric constant with a ϵr = 16, 320.21a maximum, at x = 4.5 mol% remnant polarization with a 183.47 µCcm −2 a maximum. It is confirmed that Sr can improve the properties of PZT according to the hypothesis of this study.